Running demands during top-up conditioning sessions compared to competitive matches in elite Portuguese soccer players - Ribeiro, J.; Gantois, P.; de Souza Fonseca, F.; Suarez-Arrones, L.; Viana, J.; Nakamur, F. Y. (Biology of Sport, 2025)
Soccer players who are non-starters typically experience reduced match loads, which can hinder their physical fitness and match readiness over time. This study aimed to investigate the running demands accumulated during top-up sessions in comparison to soccer matches. Twenty-six outfield soccer players from an elite Portuguese soccer team participated in this study. The following running variables were recorded: total distance (TD), running (14.4 to 19.7 km · h-1), high-speed running (HSR: 19.8 to 25.1 km · h-1), sprinting (= 25.2 km·h-1) distances, number of sprints (counts), number of accelerations (ACC; 2-3 m·s-2 and > 3 m·s-2), decelerations (DEC; 2-3 m·s-2 and > 3 m·s-2), and player load. A linear mixed-effects model was used to examine differences between top-up sessions and matches. Overall, no starters accumulated lower running load during top-up sessions than matches for most of the variables analyzed, but in particular TD (p < 0.001; ES range 2.46 to 3.74), running (p < 0.001; ES range 2.93 to 3.90), HSR (p < 0.001; ES range 2.21 to 3.47), sprints events (p < 0.001; ES range 1.16 to 2.76), ACC > 3 m·s-2 (p < 0.005; ES range 0.98 to 1.37), DEC > 3 m·s-2 (p < 0.001; ES range 1.91 to 2.66), and player load (p < 0.001; ES range 2.34 to 3.23). Therefore, non-starters accumulated less than half of the total match distance for most of the running metrics during top-up sessions. These findings suggest that compensatory training should be designed to more closely replicate match demands, with particular attention to high-intensity demands, such as HSR and sprints.